Pragmatic Analysis: Verbal Politeness Norms Used in Requests by Young People at UNAH-CU - Funez, Aida (2026)
This article analyzes the verbal politeness norms used in requests made by young people at the National Autonomous University of Honduras, Ciudad Universitaria (UNAH-CU). The study is framed within communicative pragmatics and aims to describe the linguistic strategies employed to preserve the interlocutors’ social image in everyday contexts. It draws on Brown and Levinson’s (1987) model of positive and negative politeness and on Blum-Kulka, House, and Kasper’s (1989) coding scheme for requests, adapted by Trosborg (1995). The main hypothesis posits that women use more verbal politeness strategies than men, regardless of social distance. The research follows a qualitative-descriptive approach and applies questionnaires to 120 students (60 men and 60 women). Findings reveal that women tend to use more mitigators, justifiers, and politeness markers in some situations, while men favor more direct requests. This study contributes to understanding linguistic dynamics among Honduran university students and provides a framework for future studies on verbal politeness in Latin American sociocultural contexts.